Analisis Makna Simbolik Tradisi Pakkio’ Bunting Pada Perkawinan Adat Suku Makassar - Nosakros Arya Arya; Teguh Ardiansyah Sabir; Dhia Naufalia Ilmi; Akhyar (Connected: Jurnal Ilmu Komunikasi, 2022)
Marriage is an essential thing for a person—likewise, the views of the Bugis people. According to the opinion of the Bugis people, marriage is not the union of the two brides and groom in a husband-wife relationship. Still, marriage is a ceremony that aims to unite two prominent families that have previously become closer or deeper. The depth of the meaning of marriage for Bugis makes a series of ceremonies to respect the perka. In the customary marriage of the Bugis Makassar, there is a tradition that the community has carried out. One of those traditions is